180k views
5 votes
Rewrite the equation x + y + 3 = –2x + 4y + 18 into standard form (ax + by = c).

User Maksimov
by
6.2k points

2 Answers

3 votes

Standard form : Ax + By = C

x + y + 3 = –2x + 4y + 18

x + 2x + y - 4y = 18 - 3

3x - 3y = 15

Answer

3x - 3y = 15


User Shinil
by
5.7k points
2 votes

Answer:

Standard form of (ax + by = c) given equation is -3x + 3y = 3

Explanation:

Given equation: x + y + 3 = –2x + 4y

Standard form of equation: ax + by = c

Solution:

x + y + 3 = –2x + 4y

= -2x + 4y = x + y +3

By subtracting x and y from both sides of equation:

= -2x - x + 4y - y = x + y + 3 - x - y

= -3x +3y = 3

So standard form of equation is -3x + 3y = 3 in which -3 is a and 3 is b and 3 is equal to c.



User Paril
by
6.2k points